Identification and reduction of non-value adding activities in the precast concrete construction projects in Singapore - Wu, Peng; Feng, Y.; Zhong, Y. (Association of Researchers in Construction Management, 2012)
Prefabrication systems are believed to have the potential for better environmental performance and have been adopted by the construction industry to meet the challenges posed by global climate change. However, there remains many areas in the prefabrication systems that can be improved in order to reduce carbon emissions, such as site layout, work flow and inventory control. This research therefore aims to identify the non-value adding activities that can be eliminated to reduce carbon emissions in the precast concrete construction projects in Singapore. A weighted factor model comprising 30 contractors in the Singapore construction industry is adopted. Two stages in the precast concrete installation cycle are investigated using the weighted factor model, which are site layout management and delivery management. The results indicate that there are many non-value adding activities in the precast concrete installation cycle that contribute to an increase in the level of carbon emissions, such as large storage area and lack of just-in-time sourcing. The analysis provides good practice guidance and can be used as a checklist for contractors to achieve low-carbon installation. The results will also be useful for regulatory agencies to provide recommendations for the construction industry to reduce carbon emissions.